Death, The Strange Familiar (Meaning of Death from Iranian Nurses' Perspective): A Qualitative Study - A. Zargham; R. Mohammadi; F Oskouei (Iran University of Medical Sciences, 2007)
Background & Aim: Despite tremendous progressions in medical science and technology, there is no way yet to escape death. Logical attitudes of nurses toward death could be influential on care giving of dying patients and their families. If the health care professionals view death as a terrible and dire thing, they couldn't handle patients' death in a fair and effective manner. So, it seems that the first step toward designing an appropriate care and support system for dying patients and their family is exploring nurses' beliefs and point of views. The aim of this study was to determine the concept of death from Iranian nurses' perspective to reach a new explanation for this concept in community.   Material & Method: This study was conducted by qualitative research approach. Data collection was done via semi structured interviews with 12 Nurses from 4 hospitals. They had 2 to 18 years working experience in emergency departments, ICUs, CCUs and oncology wards. All interviews were taped, and then transcribed on paper and analyzed using Strauss and Corbin method. Four main categories emerged: non avoidable ending, ambiguity and uncertainty, feedback for personal behaviors, and changing attitudes toward life and death.   Results: This study showed that one of the most important ideas which help nurses to better dealing with death is belief in life after death. Recognizing death as fate of all lives could also bring peace to the man. This sort of attitude gives the nurse a peace of mind which helps to make dying patients and their families comfortable. The perspective of death which emerged from nurses' perspectives in this research is a spiritual one. They believed that their occupation with nursing reinforces this attitude and decreases their uncertainty about life after death.   Conclusion: This study provides a deep understanding about nurses' point of view about death which could be a base for nursing education about death and dying